127k views
9 votes
Please help!

Write the sum, and then write an equivalent expression by collecting like terms and removing parentheses whenever possible.

a. -4 and 4b + 4
b. 3x and 1 -3x

1 Answer

4 votes

Answer:

Does this problem have a picture, I just need to make sure I am seeing everything correctly thanks!

Explanation:

a. -4 and 4b + 4 = 4b

-4 and 4b + 4 = -4 + (4b + 4) = 4b + (4 - 4) = 4b + 0 = 4b

b. 3x and 1 - 3x = 1

3x and 1 - 3x = 3x + (1 - 3x) = 1 + (3x - 3x) = 1 + 0 = 1

User Mysl
by
5.0k points